Audit. - Bellavance, Guy; Berchem, Otto; Blase, Christoph; Boomgaard, Jeroen; Bourdieu, Pierre; Chapman, Christopher; Coley, Nathan; Durkheim, Emile; Einarsson, Gardar Eide; Fabricius, Jacob; Frankle, Robert; Hoffman, Jan; et al. (Luxembourg :, Casino Luxembourg - Forum d'Art Contemporain, 2001)
Berchem, Otto ; Burden, Chris ; Coley, Nathan ; Einarsson, Gardar Eide ; Elmgreen, Michael ; Dragset, Ingar ; Friedl, Peter ; Moffatt, Tracey ; Muntadas, Antoni ; Potrc, Marjetica ; Prum, Antoine ; Stevenson, Michael ; Visser, Barbara
Duits & Engels
Audit, Casino Luxembourg - Forum d'Art Contemporain, Luxembourg, 29.09.2001 - 02.12.2001
boek